Factors associated with successful return to work in young heart failure and ischaemic heart disease patients following index hospital admission. (11th May 2021) - Thakkar, HV; Hollingsworth, L; Enright, JA; Sanderson, S; Macfadyen, RJ; Dwyer, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Factors influencing return to remunerated work following an acute cardiac illness are poorly defined. We wished to compare the factors in our cohorts following first presentation of acute coronary syndrome(ACS) and decompensated heart failure(HF). Methods: Prospectively identified subjects, aged 18-65years, from a rehabilitation population for ACS and HF during 2018-2019 underwent a survey. Results: Of 133cases meeting inclusion criteria, 84 completed the survey(41 HF, 80% male, mean age 55years; 43 ACS, 86% male, mean age 57years). Socio-economic indexes for Areas(SIEFA) index were similar for HF(900) & ACS(909) groups, which represents 11th and 14th percentile for Australia respectively. Cardiovascular risk factors were similar except hypercholesterolemia(37% v 60%; p = 0.029) was more common in ACS. Many subjects did not continue beyond Yr12, (54% HF v 30% ACS; p = 0.029). A majority of ACS cases returned to work as compared with HF(70% v 44%; p = 0.017)(Figure). On multivariate analysis, male gender[p = 0.031;OR 13.71 (1.28-147.36)]; access to financial benefits[p < 0.001;OR 22.75 (4.31-119.99)] and a desire to return to work [p = 0.014;OR 12.1 (1.67-87.82)] were associated with successful return to work (Table). Limitations: Our study has small numbers so will be difficult to generalise to a wider population. We do show a signal towards the complex interplay of the social and individual factors in determining return to work. Further larger studies are required to tease out the differences between the individual factors to help predict return to work in the Australian context. Conclusion: Successful return to work for patients with first presentation of ACS or HF could not be reliably predicted. Patients with ACS returned to work more often than HF. In HF patients who do n to return to work, recurrent symptoms, individual motivation, social support and access to financial benefits have a complex interplay.